Biomass and carbon stocks in mangrove ecosystems of Kerala, southwest coast of India - Harishma, K. M.; Sandeep, S.; Sreekumar, V. B. (Ecological processes, 2020)
Background Mangroves are important tropical carbon sinks, and their role in mitigating climate change is well documented across the globe. However, the ecosystem carbon stocks in the mangroves of India have not been studied comprehensively. Data from this region is very limited for providing sufficient insights and authentic evaluation of carbon stocks on a regional scale. In this study, we evaluated the ecosystem carbon stock and its spatial variation in mangroves of Kerala, southwest coast of India. Results The mean biomass stored in mangrove vegetation of Kerala is 117.11 ± 1.02 t/ha (ABG= 80.22 ± 0.80, BGB =36.89 ± 0.23 t/ha). Six mangrove species were found distributed in the study area. Among the different species, Avicennia marina had the highest biomass (162.18 t/ha) and least biomass was observed in Sonneratia alba (0.61 t/ha). The mean ecosystem carbon stock of mangrove systems in Kerala was estimated to be 139.82 t/ha, equivalent to 513.13 t CO 2 e/ha with the vegetation and soil storing 58.56 t C/ha and 81.26 t C/ha respectively. Conclusion The present study reveals that Kerala mangroves store sizable volume of carbon and therefore need to be preserved and managed sustainably, to retain along with the increase in carbon storage. This features the need of broadening mangrove cover as well as restoring deteriorated land in the past 50 years. Although mangrove forests in this region are protected by the Kerala Forest Department, they have been frequently facing illegal encroachment, prawn cultivation, and coastal erosion.